A Heuristics-Based Framework for User Satisfaction Evaluation Across the Lifecycle of Information Systems Projects - Guimarães, Keslley W. C.; Silva, Gabriele P. da; Takagi, Nilton; Souza, Patricia C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248774, 2026)
Research Context: User satisfaction is recognized as a key success criterion in Information Systems (IS) projects. In the IS project context, continuously monitoring this criterion throughout the project lifecycle can reduce training and rework costs, enhance user experience, and prevent client loss. Scientific and/or Practical Problem: Despite its relevance, there is a lack of methods in the IS project management literature to evaluate user satisfaction during the development cycle. Existing approaches focus mainly on end-stage evaluations, limiting timely adjustments and evidence-based decision-making during project execution. Proposed Solution and/or Analysis: This paper proposes a framework for assessing user satisfaction in IS projects through three stages: expectation elicitation, expert inspection, and post-use verification. All stages are supported by questionnaires derived from usability heuristics to guide structured evaluation and comparison. Related IS Theory: The study is grounded in the Information Systems Success Model, which identifies user satisfaction as an essential dimension of project success, and integrates principles from Human–Computer Interaction (HCI). Research Method: An exploratory review of relevant literature was conducted, followed by the design of the proposed framework and its validation through three instrumental case studies across different organizational domains. Summary of Results: The results indicate that the proposed framework enables the evaluation of user satisfaction during system development, allowing early identification of usability issues and improvement opportunities. Contributions and Impact to the IS Area: This work contributes to IS project success management by operationalizing user satisfaction as a continuous and measurable criterion, ensuring its systematic verification throughout the project lifecycle and providing managers with a practical tool for evidence-based decision support.